Thermal performance analysis of a new refrigerant-heated radiator coupled with air-source heat pump heating system. (1st August 2019) - Shao, Suola; Zhang, Huan; You, Shijun; Zheng, Wandong; Jiang, Lingfei
Highlights: A new type of refrigerant-heated radiator coupled with ASHP system is proposed. The heat flux of this new radiator varies from 89.2 W/m 2 and 211.4 W/m 2 . The COP of the system with new radiator could be as high as 3.5 during the tests. The system with RHR is superior in indoor thermal with the reasonable PMV. Abstract: Air-source heat pump (ASHP) is considered to be one of the most energy conservation heating system in the areas without district heating. To improve the performance of the ASHP heating system, a new type of refrigerant-heated radiator (RHR) is proposed. As a new direct-condensation terminal, it avoids the secondary heat exchange and is conducive to reduce the condensing temperature and heat loss. Experiments are conducted to investigate the temperature and operating characteristics of the heating system with the new radiator, as well as the thermal performance and system efficiency during the heating period. The results indicate that the radiator has favorable thermal performance with the heat flux varies from 89.2 W/m 2 to 211.4 W/m 2 during the testing period. Heat storage material is employed in the radiator to maintain the stability of indoor thermal environment during the defrosting process, and it can provide the heat of 750.9–1699.6 kJ. The convective heat transfer coefficient of the RHR was regressed and the coefficient of performance (COP) of the new system could be as high as 3.5 during the tests. Meanwhile, the ASHP heating system with RHR is superior in the indoor thermal comfort with the reasonable indoor PMV and lower vertical temperature gradient. It is demonstrated that the refrigerant-heated radiator matches well with the heat pump heating system, and can effectively improve the thermal performance and indoor thermal environment, as well as it has significant effects on the application of ASHP in the severe cold areas.